2012
DOI: 10.1111/j.1754-9485.2012.02366.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphoma in immunocompetent patients: A retrospective review of MRI features

Abstract: The vast majority of cases of PCNSL in immunocompetent patients have lesions contacting a CSF surface, enhancement and restricted diffusion with no necrosis. These features should alert radiologists to the diagnosis of PCNSL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…These lesions are predominantly supratentorial (Koeller et al, 1997;Buhring et al, 2001). Ring like enhancement is rarely observed in immunocompetent patients, but can be commonly found in immunocompromised patients (Johnson et al, 1997;Haldorsen et al, 2008;2009;, Sutherland et al, 2012. In our study ring enhancement was observed in only two cases, one of which was labeled as Tuberculoma on radiological assessment.…”
Section: Discussionmentioning
confidence: 41%
“…These lesions are predominantly supratentorial (Koeller et al, 1997;Buhring et al, 2001). Ring like enhancement is rarely observed in immunocompetent patients, but can be commonly found in immunocompromised patients (Johnson et al, 1997;Haldorsen et al, 2008;2009;, Sutherland et al, 2012. In our study ring enhancement was observed in only two cases, one of which was labeled as Tuberculoma on radiological assessment.…”
Section: Discussionmentioning
confidence: 41%
“…It has been reported that adult PCNSL occurs in supra tentorial location in majority of patients with posterior fossa as a location of tumor only in 7% of the cases[6]. Only 3% cases have been reported to have a brainstem involvement and majority of such lesions are of T-cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast enhanced MRI is the preferred imaging modality in these cases of PCNSL. Approximately 90% of these cases present with contrast enhancing lesions[6]. Ring like enhancement is rarely observed in immune competent patients, but commonly found in immune compromised patients[7].…”
Section: Discussionmentioning
confidence: 99%
“…According to Summary of the nine reported cases and our case of primary isolated lymphoma within the 4 th ventricle a consideration of PCNSL should be warranted if contrast enhancement image shows homogeneous enhancement without necrosis. Besides, Magnetic Resonance Spectrum (MRS), in combination with hyper intensity on CT [10] is helpful for differential diagnosis between PCNSL and other brain tumors. By the way, due to the special location, excision was the preferred choice for PCNSL in the fourth ventricle.…”
Section: Discussionmentioning
confidence: 99%